The Effect Of Islamic Corporate Governance, Current Ratio, Total Asset Turnover And Intellectual Capital On Profitability (Study on Sharia Commercial Banks registered with the Financial Services Authority (OJK) for the 2018-2022 period) - Faisal aristama; Hanif Hanif; Muhammad Iqbal; Fithriah Wardi (LP2M IAIN Palopo, 2024)
Profitability is a measurement of the financial performance of Islamic banks, which is the company's ability which is shown through the management of the use of total assets related to the company's operational activities. The better the management of total assets, the higher the profit obtained. This study aims to analyze the effect of Islamic corporate governance, current ratio, total asset turnover and intellectual capital on profitability. The companies studied are Sharia Commercial Banks as many as 10 companies for five years with the period 2018-2022.The method used in this study is the multiple linear regression analysis method with the help of the SPSS 23 program. Data collection techniques are carried out with documentation techniques with secondary types of data, namely in the form of financial statements of Islamic commercial bank companies registered with the Financial Services Authority for the 2018-2022 period.The results in this study show that Islamic corporate governance has a positive effect on profitability, current ratio has a positive effect on profitability, total asset turnover has a positive effect on profitability and intellectual capital has a positive effect on profitability